2010
DOI: 10.1002/anie.201000633
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Design Rules for DNA‐Mediated Programmable Colloidal Crystallization

Abstract: The assembly of DNA-programmable colloidal crystals is presented, where the sizes of nanoparticles used vary from 5 to 80 nm and the lattice parameters of the resulting crystals vary from 25 to 225 nm. A predictable and mathematically definable relationship between particle size and DNA length is demonstrated to dictate the assembly and crystallization processes, creating a set of design rules for DNA-based nanoscale assembly. ** We acknowledge George Schatz for helpful discussions regarding the theoretical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
161
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 23 publications
4
161
0
Order By: Relevance
“…This suggests that the kinetics of DNA bond formation may be of great importance to crystallization. A surprising result from prior studies is that the thermodynamic product of this reorganization can be described using the hybridization behavior and thermodynamic properties of free oligonucleotides, if one takes into account the increased oligonucleotide and salt concentration (relative to the bulk) found at the surface of a PAE (16,17). In this work, we hypothesize that the kinetics of particle reorganization in superlattices can be explained by examining the kinetics of free oligonucleotides.…”
Section: Significancementioning
confidence: 78%
See 2 more Smart Citations
“…This suggests that the kinetics of DNA bond formation may be of great importance to crystallization. A surprising result from prior studies is that the thermodynamic product of this reorganization can be described using the hybridization behavior and thermodynamic properties of free oligonucleotides, if one takes into account the increased oligonucleotide and salt concentration (relative to the bulk) found at the surface of a PAE (16,17). In this work, we hypothesize that the kinetics of particle reorganization in superlattices can be explained by examining the kinetics of free oligonucleotides.…”
Section: Significancementioning
confidence: 78%
“…Although other designs have also been used to generate colloidal crystals, the DNA design strategy used in this work enables exquisite control over crystal symmetry and lattice parameters (6,7,14,16), both of which have been difficult to realize experimentally to the same degree with systems where interparticle connections comprise long DNA linkages with large regions of single-stranded DNA (21,22). This design is also crucial for the systematic study reported herein, where DNA bond kinetics between different crystal samples can be more readily compared without concerns about variations in DNA length or solution temperature, both of which can significantly impact the mobility, structure, and orientation of DNA strands containing long singlestranded regions.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…With such methods, one can make architectures with well-defined lattice parameters (6)(7)(8)(9)(10)(11)(12), symmetries (4,8,10,12), and compositions (10,12,13), but to date they have been confined primarily to the use of hard inorganic nanoparticles (NPs) or highly branched pure nucleic-acid materials (2,14,15). In contrast, Nature's most powerful and versatile nanostructured building blocks are proteins and are used to effect the vast majority of processes in living systems (16).…”
mentioning
confidence: 99%
“…Here, we introduce a new method for effecting protein crystallization by trading protein-protein interactions for complementary oligonucleotide-oligonucleotide interactions. By using different proteins functionalized with the appropriate oligonucleotides, along with the design rules introduced for inorganic systems (7,8,28), we show that different combinations of DNAfunctionalized enzymes, and enzymes and inorganic NPs, can be assembled deliberately into preconceived lattices and, in some cases, well-defined crystal habits. Importantly, the enzymes retain their native structures and catalytic functionalities after extensive modification of their surfaces with DNA and assembly into crystalline superlattices.…”
mentioning
confidence: 99%